2021
DOI: 10.1136/bmjopen-2021-054284
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of burnout among nurses during COVID-19: a cross-sectional study in hospitals in central Uganda

Abstract: ObjectiveTo determine the prevalence of burnout and associated factors among nurses during COVID-19 in central Uganda.DesignA cross-sectional design.SettingNurse from one referral and four general hospitals. These were reception centres and cared for patients with COVID-19 in central Uganda.Participants395 nurses.Main outcome measuresBurnout scores.ResultsOf the total 395 participants, 65.1% (n=257) were female; 40% (n=158) had a diploma; 47.1% (n=186) were single; and 39.2% (n=155) had worked for 11–15 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 48 publications
(85 reference statements)
9
43
2
Order By: Relevance
“…In contrary to studies suggesting that inadequate PPE can be a considered a principal stressor increasing the burnout ( 19 , 63 ), our findings showed that those wearing adequate PPE while interacting with COVID-19 patients had higher personal burnout. As frontline HCWs are the first responders for COVID-19 patients, they can be physically and mentally exhausted during their prolonged wear of PPE given its limitations of comfort and reduced ability to communicate.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrary to studies suggesting that inadequate PPE can be a considered a principal stressor increasing the burnout ( 19 , 63 ), our findings showed that those wearing adequate PPE while interacting with COVID-19 patients had higher personal burnout. As frontline HCWs are the first responders for COVID-19 patients, they can be physically and mentally exhausted during their prolonged wear of PPE given its limitations of comfort and reduced ability to communicate.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with previous research which shows a correlation between burnout and age [ 34 ]. However, contrary to our findings, other studies did not find a relationship between burnout and age [ 35 , 36 ]. The disparity in findings may be attributed to differences in measurements of burnout and the timing of conduct of the study.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, the study by Batayneh et al [ 35 ] used the Maslach Burnout Inventory (MBI) while we used the Stamm's Professional Quality of Life (ProQOL V-5) to measure burnout. Relatedly, unlike our study, the study by Kabunga and Okalo [ 36 ] was conducted in the context of Coronavirus disease 2019 (COVID-19). Nonetheless, our results suggest a need to devise mechanisms to protect younger nurses against workplace-related factors such as heavy workload that predispose them to burnout.…”
Section: Discussionmentioning
confidence: 96%
“…A US study conducted over the same time span using a single item burnout measure found high burnout in 66% of nurses [ 43 ]. A study of nurses in Uganda in May–June 2021 using the ProQOL instrument found high burnout in 40% [ 44 ]. The use of different measurement instruments precludes direct comparison, but these studies confirm multiple reports of high rates of burnout in nurses.…”
Section: Discussionmentioning
confidence: 99%